2010
DOI: 10.1089/sur.2009.047
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of Empiric Antibiotic Utilization: Establishing Benchmarks

Abstract: Aim: We critically evaluated empiric antibiotic practice in the surgical and trauma intensive care unit (STICU) with three specific objectives: (1) To characterize empiric antibiotics practice prospectively; (2) to determine how frequently STICU patients started on empiric antibiotics subsequently have a confirmed infection; and (3) to elucidate the complications associated with unnecessary empiric antibiotic therapy. Methods: We collected data prospectively using the Surgical Intensive Care-Infection Registry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…A prospective evaluation in a surgical and trauma ICU found that of 312 patients receiving empirical therapy only 25.6% were found to have an infection [14] . The empirical antibiotic group had a greater number of total antibiotic days, was more likely to develop a confirmed infection, and had more resistant organisms and a higher ICU mortality rate [14] . These results highlight the relevance of the observation that empirical therapy contributed substantially to antimicrobial consumption in this study.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A prospective evaluation in a surgical and trauma ICU found that of 312 patients receiving empirical therapy only 25.6% were found to have an infection [14] . The empirical antibiotic group had a greater number of total antibiotic days, was more likely to develop a confirmed infection, and had more resistant organisms and a higher ICU mortality rate [14] . These results highlight the relevance of the observation that empirical therapy contributed substantially to antimicrobial consumption in this study.…”
Section: Discussionsupporting
confidence: 60%
“…Empirical therapy was the most common indication for prescribing, accounting for 50% of antimicrobial courses and for 54% of consumption. A prospective evaluation in a surgical and trauma ICU found that of 312 patients receiving empirical therapy only 25.6% were found to have an infection [14] . The empirical antibiotic group had a greater number of total antibiotic days, was more likely to develop a confirmed infection, and had more resistant organisms and a higher ICU mortality rate [14] .…”
Section: Discussionmentioning
confidence: 99%
“…It suffers from many of the same problems as mortality, especially with secular trends in developed countries where an emphasis has been placed on early discharges. Attempts to discontinue or transition to oral antimicrobial therapy from parenteral therapy has, perhaps, the strongest relationship to length of stay [ 41 , 67 , 68 ••, 69 ]. Rather than hospital length of stay, some interventions use intensive care unit length of stay as a surrogate for clinical improvement [ 68 ••, 69 ].…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…The impact of this missingness being that several studies had to exclude data in analysis [106,111,124,125]. Challenges with data quality were described at point of data capture and extraction [30,33,34,40,63,84,87,90,101,108,118,120,143]. Ability to accurately measure processes of care associated with the indicator (e.g., time of antibiotic administration in the context of recognition of infection/ prescription of antibiotics) hindered utilization of the indicator in care evaluations [32,46,50,51,58,98,103,120,144,145].…”
Section: Operationalmentioning
confidence: 99%